2018
DOI: 10.14419/ijet.v7i4.30.22068
|View full text |Cite
|
Sign up to set email alerts
|

Recycled Concrete Aggregates as a Filter for Removal of Phosphorus in Synthetic Wastewater

Abstract: This paper assesses of recycled concrete aggregates as a filter for removal of phosphorus in synthetic wastewater. Recycled concrete aggregate used as a filter system emerged as an alternative technology for phosphorus removal. This can overcome the problem of construction site waste by converting the waste into something valuable products. Thus, this study aim to determine the percentage of Phosphorus removal by using two different size of Recycled Concrete Aggregate which is (5 mm to 10 mm) and (25 mm to 30 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 8 publications
(11 reference statements)
0
2
0
Order By: Relevance
“…These findings are inconsistent with previous studies which confirmed that the primary and secondary treatment processing of sewage wastewater is insufficient for removing nutrients. 5,6 Moreover, the results revealed that the wastewater generated from the wastewater treatment plant in the study area should be subjected to a treatment process to minimize the concentrations of the pollutants before the final disposal into the environment. Based on SEM analysis of the slime sample attached on the rock surface collected from the VFASSF, the nitrifying bacterial cells had rod, coccus and spherical shapes, as found previously 18,19 ( Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings are inconsistent with previous studies which confirmed that the primary and secondary treatment processing of sewage wastewater is insufficient for removing nutrients. 5,6 Moreover, the results revealed that the wastewater generated from the wastewater treatment plant in the study area should be subjected to a treatment process to minimize the concentrations of the pollutants before the final disposal into the environment. Based on SEM analysis of the slime sample attached on the rock surface collected from the VFASSF, the nitrifying bacterial cells had rod, coccus and spherical shapes, as found previously 18,19 ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…4 Rock filter (RF) is an alternative natural treatment method for removing nutrients from wastewater. 5,6 The method is relatively simple, cost-effective and efficient in removing nutrients from large quantities of wastewater. 7 Moreover, the method is more applicable to treating wastewater from small communities owing to the simplicity of construction, low initial cost, and the potential for extremely low operation and maintenance costs and energy requirements.…”
Section: Introductionmentioning
confidence: 99%